‘Spectator’ or Player’? Labor Movements in Post New-Order Indonesian Electoral Politics - Tunjung Sulaksono; Kuskridho Ambardi (Jurnal Studi Pemerintahan, 2019)
This study proves that the change in the structure of political opportunities alone is not enough to provide encouragement for social movements to succeed in electoral politics. The case of the labor movements in electoral politics in post-New Order Indonesia is proof of this. Even though it has a very large number of potential to become a large force of electoral politics and ability to mobilize masses, the labor movements in Indonesia is merely a spectator, not a player in electoral politics. There are four factors that cause this failure. The first is fragmentation among labor movements which were created as a result of the opening of political opportunities after the New Order. Second, labor apathy towards labor parties and labor cadres who run for elections. As a result, none of the labor parties succeeded in gaining seats in three elections in Indonesia after the New Order. Thirdly, repression and negative stigmatization to the labor movements by the New Order Regime had succeeded in preventing labor movement to consolidate themselves and to gain significant votes in elections. Fourth, increasingly severe requirements for party establishment and participation in elections. While in many places the opening of political opportunity structure is a determining factor in the success of social movements in electoral politics, the case of the labor movement in Indonesia proves otherwise. The opening up of a political opportunity structure has become a trap that hinders the success of labor movements in electoral politics.